Respostas

2014-03-20T18:26:33-03:00
$\lim_{x\rightarrow 3} \frac{{ \sqrt[3]{x}- \sqrt[3]{3} }}{ x-3}   resulta numa indeterminação do tipo  \frac{0}{0} .
Então eu posso usar a regra de L'Hospital , que diz que voce deriva em cima e em baixo.
( \sqrt[3]{x}- \sqrt[3]{3}  )' =  \frac{1}{3}   x^{ \frac{1}{3} -1} - 0 =  \frac{1}{3}   x^{ \frac{-2}{3} } = \frac{1}{3}   \sqrt[3]{ \frac{1}{x^{2}} }  }
e
(x-3)'=1

$\lim_{x\rightarrow 3} \frac{{ \sqrt[3]{x}- \sqrt[3]{3} }}{ x-3} = \lim_{x\rightarrow 3} \frac{{( \sqrt[3]{x}- \sqrt[3]{3})' }}{ (x-3)'}

=$\lim_{x\rightarrow 3} \frac{{ \frac{1}{3} \sqrt[3]{ \frac{1}{x^{2}} } }}{ 1} = \frac{1}{3}  \sqrt[3]{ \frac{1}{3^{2}} }




1 5 1